ANALISIS JOB PERFORMANCE PETUGAS SURVEILANS KESEHATAN (GASURKES) DALAM UPAYA PENGENDALIAN DBD DI KOTA SEMARANG: ANALISIS KINERJA PEKERJAAN - Hayyu Naafi Hidhayanti (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2023)
DHF Health Surveillance Personnel (Gasurkes) are officers recruited by the Semarang City Health Office to control DHF in Semarang City. The purpose of this study was to determine the job performance of DHF health surveillance officers (Gasurkes) in Semarang City, the variables involved are job descriptions, performance reviews, motivation, incentives, knowledge and skills. This type of research uses quantitative methods, with a cross sectional approach. The sampling technique uses total sampling, as many as 172 DHF Gasurkes. Data were obtained from filling out questionnaires by Gasurkes DBD according to their self-assessment. The questionnaire uses the Guttman scale and Likert scale. The results of this study show the presentation of variables with good criteria, namely: job description (58.7%), performance review (64.5%), motivation (72.7%), incentives (54.7%), knowledge (79, 1%), and skills (70.3%). There is no relationship between job descriptions and the performance of DHF Gasurkes (p-value = 0.104), there is a relationship between performance reviews and DHF Gasurkes performance (p-value = 0.024), there is a relationship between motivation and DHF Gasurkes performance (p-value = 0.046) , there is a relationship between incentives and DHF Gasurkes performance (p-value = 0.001), there is no relationship between knowledge and DHF Gasurkes performance (p-value = 0.1000) and there is no relationship between skills and DHF Gasurkes performance (p-value = 0.334) in controlling DHF in Semarang City. motivation (p-value = 0.037 and exp value (?) = 2.192) and incentives (p-value = 0.001 and exp value (?) = 3.048) have a significant effect on the performance of the DHF Gasurkes in the identification of DHF in Semarang City. For this reason, it is hoped that motivation and incentives can be increased and used as a factor in improving the performance of the DHF Gasurkes in Semarang City. Keywords : Job performance, health surveillance personnels, dengue fever